A NEW MEASURE OF FEELINGS OF BURDEN FOR OLDER ADULTS. (11th November 2018) - Lutz, J; Katz, E; Gallegos, J; Spalding, R; Edelstein, B
Abstract: Feelings of being a burden on others may have important implications for various psychosocial variables in older adults, though little research has been conducted in this area. Perceived burdensomeness is most commonly studied as it relates to suicidal ideation (Joiner, 2005), where research strongly supports a critical role of burdensomeness in suicidal ideation. However, a broader range of feelings of burden, beyond believing others would be better off if one was dead, is important to measure among older adults. The purpose of this study was to develop a new measure of feelings of burden on others for older adults. We developed a 25-item measure, utilizing expert consultation and exploratory factor analysis, in an initial sample of 219 participants. We examined the psychometric properties of the measure with 192 participants. The measure exhibited convergent validity with moderate to strong correlations with the Geriatric Depression Scale (r = .69, p < .001), Beck Hopelessness Scale (r = .63, p < .001), the Geriatric Suicide Ideation Scale (r = .80, p < .001), and the Interpersonal Needs Questionnaire-15 Perceived Burdensomeness subscale (r = .83, p < .001). Internal consistency was strong (Cronbach's alpha = .97). This measure exhibits strong psychometric properties in community-dwelling older adults in the U.S., and measures a broader continuum of feelings of burden. This measure opens the door for the study of feelings of burden among older adults in a variety of contexts (e.g., end-of-life decision making, development of psychopathology).